Speeds of sound and densities in imidazolium-based ionic liquids under elevated pressures: New experimental data and modelling by spinodal method and CP-PC-SAFT. (January 2023) - Pilarz, Jeremiasz; Feder-Kubis, Joanna; Postnikov, Eugene; Melent'ev, Vyacheslav V.; Ryshkova, Olga S.; Korotkovskii, Vadim I.; Radchenko, Anton K.; Wasiak, Michał; Polishuk, Ilya; Chorążewski, Mirosław
Highlights: Three ionic liquids [ C 2 -im-C1 OCn ][NTf2 ] (n = 6, 8, 10) were physiochemically tested. Their sound velocities were measured in wide T -P range. These data were modelled by spinodal method and CP-PC-SAFT EoS. Abstract: In this study reports a comprehensive physicochemical experimental characterization of a homologous series of ionic liquids containing 3-ethyl-1-alkoxymethylimidazolium bis(trifluoromethylsulfonyl)imide with linear n -alkyl chains in an alkoxymethyl substituent from the hexyl up to the decyl group. An influence of the n -alkyl chain length on the thermophysical properties was investigated in the temperature and pressure ranges 293.75 – 373.25 K and 1.019 – 1962 bar. Accuracies of the Critical Point-Based Perturbed-Chain Statistical Associating Fluid Theory (CP-PC-SAFT) and the spinodal method in modelling these data were compared.